Understanding Cadre Coping Mechanisms in Utilizing Digital Tools for Stunting Intervention Programs - Batubara, Astriana Marta; Februhartanty, Judhiastuty; Iswarawanti, Dwi Nastiti (Jurnal Kesehatan Masyarakat, 2025)
Digital tools have been increasingly adopted in health services within the years. Cadres are now expected to integrate various digital tools into their routine practices to enhance the effectiveness, accuracy, and reach of stunting prevention efforts. This qualitative study explores the coping mechanisms employed by community health cadres in Sumedang District, Indonesia, as they adapt to digital platforms for stunting intervention. In-depth interviews with cadres revealed three primary adaptive strategies: workload management through task delegation, reliance on peer and family support to overcome digital literacy barriers, and the formation of informal learning networks for knowledge sharing. While these mechanisms highlight the resilience and adaptability of cadres, the findings also expose challenges, including increased workload, inconsistent knowledge transfer, and unequal access to training and resources. The study underscores the need for structured digital literacy training, accessible technical support, and equitable capacity-building opportunities to ensure the effective and sustainable use of digital tools in stunting prevention programs. These insights are crucial for policymakers and program implementers aiming to enhance the quality and impact of digital health interventions at the community level.